PENGARUH INTERPRETASI DALAM MENINGKATKAN KEPUASAN WISATAWAN DI MUSEUM BAHARI - Janice Papin; Yudhiet Fajar Dewantara (Journal of Innovation Research and Knowledge, 2024)
Museum Bahari is an educational tourism destination that located in DKI Jakarta which offers various collections related to maritime affairs and service. From traditional boats to VOC era ships, as well as navigation tools, binoculars, anchors, and lighthouse models. Museum Bahari also hove some marine biota collections. The research method used in this research is a quantitative approach. The total sample taken was 100 respondents. In this study, data collection was carried out using Google Form and the data was processed using the SPSS program. This study uses multiple linear regression. Based on the results of the T test, it is known that the Personal Interpretation and Non-personal Interpretation variables partially have a significant effect on visitors satisfaction. Based on the results of F test, it is known that the Personal Interpretation and Non-personal Interpretation simultaneously have a significant effect on visitors satisfaction. Based on the results of the Adjusted R Square test, a value of 18,6% is obtained where the Personal Interpretation and Non-personal Interpretation affects visitor satisfaction by 18,6% and the remaining 81,4% is influenced by variables that not examined in this study. The conclusion concluded in this study is that the Personal Interpretation and Non-personal Interpretation affect visitors satisfaction at Museum Bahari. The suggestion for Museum Bahari is to pay more attention to existing interpretations so that the Museum Bahari can minimize existing shortcomings and increase visitors satisfaction and tourists can be able to recommend to their friends, and also family. The suggestion for the next researches can examine other variables that were not examined in this study and to increase their insight and knowledge